Developing the Sixth Level of PISA-Like Mathematics Problems for Secondary School Students - Kamaliyah, Kamaliyah; Darmawijoyo, Darmawijoyo; Zulkardi, Zulkardi (Journal on Mathematics Education, 2013)
Indonesia's involvement in the Programme for International Student Assessment (PISA) is one attempt to see how far the development of educational programs in our country compared to other countries in the world. PISA results show that Indonesia is still at the lower level. This means that the ability of Indonesian students in solving problems that require the ability to review, giving reasons and communicating effectively, and solve and interpret problems in various situations is still lacking. This may be due to government policy in the presence of the National Examination (UN) in which the spread of the UN's questions are still at the lower levels of cognitive aspects that are not in line with government regulations on curriculum which suggests that the fulfillment of cognitive aspects as one of the important aspects of education. To that end, researcher conducted a study that aims to produce valid and practical the sixth level of PISA-like mathematics problems for middle school students. This study is the development research formative evaluation type. The research subjects are ninth grade students SMP Negeri 1 Palembang. Data collection techniques used are walkthrough, documentation, interviews, and tests. From the analysis it can be concluded that this research has resulted a product the sixth level of PISA-like mathematics problems. At the stage of expert review, an expert and two colleagues evaluated the problems from different aspects. Trying out at one-to-one and small group wasperformed on students with different mathematical abilities. Then at the field test stage, 26 students in one class answered the questions that were developed.